Characteristics of Serious Police Misconduct: Discerning Typologies in Three Agencies - Cubitt, Timothy I. C. (Criminal justice and behavior, 2025)
The management of police misconduct is pivotal to preserving the internal and external legitimacy of policing. Preventing misconduct relies upon a good understanding of the nature and characteristics of misconduct-prone officers. This research analyzes latent typologies of officers, who have committed career ending misconduct, in agencies from the United States, the United Kingdom and Australia. Typologies from the United Kingdom and Australia were exceptionally similar, emerging among (a) younger, less experienced officers, and (b) older, more experienced officers. Officers prone to career ending misconduct in the United States appeared more uniform, with typologies principally based on civilian characteristics and use of force. Findings support research suggesting that, while minor misconduct may be more prevalent among younger officers, the profile of officers who committed career-ending misconduct may be more linked to life-course factors than experience levels. This research holds implications for the measurement of police misconduct, and management and prevention approaches.